ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN PADA PRODUK SCARLETT MELALUI KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING (STUDI PADA MAHASISWI FEB UNARS SITUBONDO) - Murtakiyah, Wardah; Arief, Mohammad Yahya; Fandiyanto, Randika (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
Marketing has an important role in a company, for this reason, the skincare industry, which is growing rapidly from year to year, must implement good marketing management in order to produce and provide products that can meet the needs and desires of consumers. The aim of this research is to analyze and test the factors that influence consumer satisfaction with Scarlett products through purchasing decisions. This research is quantitative research. The populations in this study were female students from the Faculty of Economics and Business UNARS SITUBONDO. The sampling technique was determined using purposive sampling. The data analysis and hypothesis testing in this research used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that brand image has no significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions, promotion has no significant effect on purchasing decisions, brand image has no significant effect on consumer satisfaction, product quality has no has a significant effect on consumer satisfaction, promotion has no significant effect on consumer satisfaction, purchasing decisions have a significant effect on consumer satisfaction. The results of the indirect influence hypothesis test show that the brand image variable has no significant effect on consumer satisfaction through purchasing decisions, product quality has a significant effect on consumer satisfaction through purchasing decisions, and promotion has no significant effect on consumer satisfaction through purchasing decisions.